2005
DOI: 10.1038/sj.eye.6701864
|View full text |Cite
|
Sign up to set email alerts
|

Cystoid macular oedema and changes in retinal thickness after phacoemulsification with optical coherence tomography

Abstract: Aims To study the incidence of cystoid macular oedema and changes in retinal thickness after phacoemulsification with optical coherence tomography (OCT). Methods In all, 131 eyes of 131 patients were studied at the ophthalmology clinic at Tung Wah Eastern Hospital from September 2001 to October 2002. All the patients had clinical assessment and OCT preoperatively and at weeks 2, 4, and 8 postoperatively. The incidence of postoperative cystoid macular oedema (CMO) was evaluated. The foveal thickness (FT) and ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
63
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 15 publications
7
63
0
4
Order By: Relevance
“…The second limitation is a possible influence of cataract on the OCT measurement. 20,21 However, since only eyes with no or slight cataract were selected for this study, the influence of cataract was considered to be minimal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second limitation is a possible influence of cataract on the OCT measurement. 20,21 However, since only eyes with no or slight cataract were selected for this study, the influence of cataract was considered to be minimal.…”
Section: Discussionmentioning
confidence: 99%
“…19 As several studies showed that cataract influences on the retinal thickness measurement of OCT, we performed the baseline examination at 3 days after surgery, and the data at 3 days after surgery were regarded to be almost the same as preoperative value. 20,21 Best-corrected visual acuity and intraocular pressure (IOP) were also tested at each examination. Best-corrected visual acuity on decimal charts was converted to the logarithm of minimal angle of resolution (logMAR) scale for statistical analysis.…”
Section: Main Outcome Measuresmentioning
confidence: 99%
“…katarakt ameliyatı öncesine göre, ameliyat sonrası 2. ve 8. haftada foveal kalınlık ve santral retinal kalınlıkta istatistiksel olarak anlamlı artış saptamıştır. 37 Benzer olarak, Biro ve ark. retinal, perifoveal ya da foveal kalınlıkta, ameliyattan bir gün sonra istatistiksel olarak anlamlı fark saptamamasına karşın, 30 gün sonra istatistiksel olarak anlamlı fark saptamışlardır.…”
Section: şEki̇lunclassified
“…Katarakt tipleri arasında ise nükleer kataraktın diğer katarakt tiplerine göre ölçümleri daha fazla etkilediği belirtilmiştir. 37 Bu çalışmada ayrıca RSLT kalınlığı ölçümünü kataraktın, pupil çapından belirgin olarak daha fazla etkilediği saptanmıştır. 40 Bizim ça-lışmamızda ise tüm hastalar dilate edildikten sonra ölçümler yapıldığı için, pupil çapı etkisi değerlen-dirme dışı bırakılmıştır.…”
unclassified
“…Therefore, in 2007, an investigation aiming to quantify the macular edema induced by intracameral phenylephrine and lidocaine in phacoemulsification surgery was undertaken (Johansson, Lundberg et al 2007). Optical coherence tomography (OCT) has been used in several studies to assess the macular thickness after cataract surgery (Sourdille and Santiago 1999;Biro, Balla et al 2006;Ching, Wong et al 2006), including randomized trials to evaluate intraoperative treatments (Ball and Barrett 2006). With this highly sensitive instrument, minute postoperative macular thickness increases can be detected in a high proportion of cataract patients, also after uneventful surgery (Sourdille and Santiago 1999;Biro, Balla et al 2006).…”
Section: Macular Safetymentioning
confidence: 99%